Analysis of acoustic modem performance for long range horizontal data transmission - Pusey, G.; Duncan, Alec; Smerdon, A. (2009)
As offshore oil and gas extraction progresses towards deeper waters and more rugged terrain, a real time method of transferring monitoring data to shore without the use of sea surface infrastructure is needed. This study investigates the horizontal performance of acoustic communication to better determine its suitability for relaying data directly to land based stations. Modelling of both deep and shallow underwater acoustic propagation was performed using the ray tracing model, Bellhop. This determined that the position of the modems is important to ensure optimum signal to noise ratio due to the refraction throughout the medium. In shallow water, multipath effects including selective fading and inter-symbol interference become the dominant source of problems. Data obtained from trials off the south coast of France is studied to investigate the various mechanisms affecting the performance of the AQUAmodem from Aquatec Group Limited. The environment included a descending bathymetry from 350m to 1000m over a range of approximately 6km. Based on FSK techniques, the modems were found to work effectively despite being located in unfavourable positions for efficient transmission. Communication over the entire trial range was attained, although it was expected further could have been achieved if not for time constraints. Additionally, data obtained using the same modelling methods applied to the trial environment show a close relationship with the data recorded by the modems. The results from this study indicate several areas of interest for further experimentation that can be better suited to assess performance parameters of underwater acoustic modems. Modelling of the performance proved effective in predicting the outcome of the field trial and can be utilised to forecast any problems for future deployments. ©2009 Crown.